Influens of an intensification on bioproductivity processes in pounds of aridic zones of Daghestan - S. B. Ber; F. M. Magomayev (Юг России: экология, развитие)
Are carried out complex hydrobiological and hydrochemical researches of ponds of various categories of the Shirokol fish factory with a various degree of an intensification (feeding of a fish and fertilizer of ponds). At cultivation two year carp fishes in poly culture fish efficiency has reached 5,32 tonnes/hectares, on the average on ponds having made 1,93 tonnes/hectares. Optimum norms and frequency of entering of mineral nitric and phosphoric fertilizers, their parity is found out at entering into ponds. Influence of intensification on trophy condition of ponds and the most economic levels of an intensification is certain at cultivation of fish and commodity of fish a carp in poly culture with fishes.